Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

-8x+3y= 313x-3y= -18x=y=

Sagot :

Given the pair of simultaneous equation;

[tex]\begin{gathered} -8x+3y=3 \\ 13x-3y=-18 \end{gathered}[/tex]

We are going to use the method of elimination to solve this.

We will be eliminating the variable y first, since it has the same co-efficient in the two(2) equations.

Thus, we have:

[tex]\begin{gathered} -8x+13x=3-18 \\ 5x=-15 \\ x=-\frac{15}{5} \\ x=-3 \end{gathered}[/tex]

To solve for y, we are going to substitute for x = -3 into any of the two(2) equations.

Thus, we have:

[tex]\begin{gathered} \text{from equation i}i) \\ 13x-3y=-18 \\ 13(-3)-3y=-18 \\ -39-3y=-18 \\ -3y=-18+39 \\ -3y=21 \\ y=-\frac{21}{3} \\ y=-7 \end{gathered}[/tex]

Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.